Optimizing Green Marketing Strategy on Marketing Performance by Implementing Green Tourism Advertising - Faerrosa, Lady; Nirwana, Baiq Nadia; Coniawati, Silviana Kholi (Value : Jurnal Manajemen dan Akuntansi, 2025)
Green marketing strategies have become an essential component in enhancing the sustainability of tourism marketing performance. However, the implementation of green marketing strategies has proven to be suboptimal, leaving ample room for further research. Therefore, this study aims to identify the tourism advertising model that best moderates the role of green marketing strategies in enhancing tourism marketing performance, thereby supporting the concept of sustainable tourism. To test this research model, an experimental method was used. The researchers designed two types of tourism advertisements: one general tourism advertisement tested on 100 control samples, and the other, a tourism advertisement emphasizing environmentally friendly messages (green tourism advertisement), tested on 100 additional samples. The results of this study indicate that green marketing strategies have a positive but insignificant effect on tourism marketing performance. However, green tourism advertising can significantly enhance the influence of green marketing strategies in improving tourism marketing performance. Because this research is based on empirical evidence, the results can provide a strong basis for policymaking and developing tourism advertising concepts that are more in line with the government's agenda to promote sustainable tourism.